Deep level trapped defect analysis in CH3NH3PbI3 perovskite solar cells by deep level transient spectroscopy. Issue 5 (8th March 2017) - Heo, Sung; Seo, Gabseok; Lee, Yonghui; Lee, Dongwook; Seol, Minsu; Lee, Jooho; Park, Jong-Bong; Kim, Kihong; Yun, Dong-Jin; Kim, Yong Su; Shin, Jai Kwang; Ahn, Tae Kyu; et al.
Abstract : We report the presence of defects in CH3 NH3 PbI3, which is one of the main factors that deteriorates the performance of perovskite solar cells. Abstract : We report the presence of defects in CH3 NH3 PbI3, which is one of the main factors that deteriorates the performance of perovskite solar cells. Although the efficiency of the perovskite solar cells has been improved by curing defects using various methods, deeply trapped defects in the perovskite layer have not been systematically studied, and their function is still unclear. The comparison and analysis of defects in differently prepared perovskite solar cells reveals that both solar cells have two kinds of deep level defects (E1 and E2). In the one-pot solution processed solar cell, the defect state E1 is dominant, while E2 is the major defect in the solar cell prepared using the cuboid method. Since the energy level of E1 is higher than that of E2, the cuboid solar cell shows higher open-circuit voltage and efficiency.